An Agent-Based Evaluation Model of Students Emotional Engagement in Classroom - Mahmoud M.A.; Subramainan L.; Alsammak I.L.H.; Hussein M.H. (Science and Information Organization, 2023)
Agent based; Agent-based evaluation; Computational modelling; Emotional engagements; Emotional state; Engagement levels; Evaluation models; Misbehaviour; Student engagement; Student emotional engagement; Students